Melatonin as a promising agent to treat ovarian cancer: Molecular mechanisms - Chuffa, Luiz Gustavo de Almeida [UNESP]; Reiter, Russel J.; Lupi, Luiz Antonio [UNESP] (Oxford University Press (OUP), 2017)
Ovarian cancer (OC) has the highest mortality rate of all gynecological cancers, and most patients develop chemoresistance after first-line treatments. Despite recent advances, the 5-year relative survival is ~45% for all OC subtypes, and invasive epithelial OC has only a 17% survival rate when diagnosed at a late stage. Identification of new efficacious molecules or biomarkers represents important opportunities in the treatment of OC. The pharmacological and physiological properties of melatonin indicate this agent could be useful against OC progression and metastasis. In normal cells, melatonin has potent antioxidant and anti-apoptotic actions. Conversely, melatonin has pro-oxidant as well as anti-proliferative, anti-angiogenic and immunomodulatory properties in many cancer types including hormone-dependent cancers. Although melatonin receptors have been identified in OC cells, the exact mechanism by which melatonin induces anticancer activities remains incompletely understood. Clinical studies have reported negative correlation between aggressiveness of OC and serum levels of melatonin, reinforcing the idea that melatonin may be a critical factor determining OC development. In vitro and in vivo studies suggest melatonin differentially regulates multiple signaling pathways in OC cells. This focused review explores the potential mechanisms of action of melatonin on cultured OC cells and in experimental models of OC in an attempt to clarify how melatonin modulates the signaling pathways involved in cancer cell apoptosis, survival, inflammation, proliferation and metabolic processes. Based on the evidence presented, we feel that melatonin, as an agent that controls cellular signals associated with malignancy, may be beneficial in combination with other therapeutics for OC treatment.